Malawi’s agrifood system: Transformation and environmental impacts - Diao, Xinshen; De Weerdt, Joachim; Fang, Peixun; Jones, Eleanor; Nagoli, Joseph; Pauw, Karl; Thurlow, James (International Food Policy Research Institute, 2025)
This paper is an update of Country Brief 8 in the series of Agrifood System Diagnostics coauthored by De Weerdt et al. (2023). The important addition from the previous country brief is a new section assessing agriculture’s environmental footprint, focusing on water use and greenhouse gas (GHG) emissions by subsector and over time. Unlike the previous version, this brief does not include a forward-looking analysis—using IFPRI’s Rural Investment and Policy Analysis (RIAPA) model (IFPRI 2023)—of the contribution of productivity growth in agricultural value chains on agrifood transformation, employment, and socioeconomic outcomes. For a recent and extensive value chain ranking analysis that incorporates RIAPA modeling results, readers are referred to Pienaar et al. (2023).